2015
DOI: 10.1186/s40199-015-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of Crataegus oxyacantha extract, aerobic exercise and their combination on the serum levels of ICAM-1 and E-Selectin in patients with stable angina pectoris

Abstract: BackgroundAdhesion molecules play an important role in the development and progression of coronary atherosclerosis. The aim of this study was comparing the effect of Cratagol herbal tablet, aerobic exercise and their combination on the serum levels of Intercellular adhesion molecule (ICAM)-1 and E-Selectin in patients with stable angina pectoris.MethodsEighty stable angina pectoris patients aged between 45 and 65 years, were randomly divided into four groups including three experimental groups and one control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…As can be seen, most of the effective components of these plants are from phenolic compounds, which besides having antifungal activities have mostly antioxidant properties [64][65][66][67][68][69]. Antioxidants are beneficial compounds which are effective against a wide variety of diseases [70][71][72][73][74][75]. Hence, each individual plant, other than for treating fungal infections, might be used for other diseases, such as gastrointestinal, cardiovascular and/or immunological disorders [76][77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen, most of the effective components of these plants are from phenolic compounds, which besides having antifungal activities have mostly antioxidant properties [64][65][66][67][68][69]. Antioxidants are beneficial compounds which are effective against a wide variety of diseases [70][71][72][73][74][75]. Hence, each individual plant, other than for treating fungal infections, might be used for other diseases, such as gastrointestinal, cardiovascular and/or immunological disorders [76][77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al (2015) reported that a combination of aerobic, resistance and traditional Korean dance exercises for 12 weeks (three days a week) decreased the E-selectin and vascular adhesion molecules 1 in old women (22). In a study by Jalaly et al (2015), 12-week aerobic exercise reduced the levels of intercellular adhesion molecules 1 and E-selectin in patients with angina pectoris (23). In a study, Hamedinia and Haghighi (2007 investigated the effect of endurance and resistance exercise on circulating soluble adhesion molecules in obese men.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional medicine and phytomedicine have always been an important solution for the treatment and prevention of various diseases [14][15][16][17][18]. Medicinal plants and their therapeutic uses are very common in Iran and other parts of the world [19,20].…”
Section: Introductionmentioning
confidence: 99%